HOW FUTURE PEDAGOGUES (PEDAGOGY STUDENTS) UNDERSTAND WHAT IS GOOD FEEDBACK - Žibėnienė, Gintautė (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
The aim of this article is to reveal what is good feedback in the opinion of future teachers (pedagogy students). The topic received a lot of attention in the scientific literature due to the training process being carried out during the COVID-19 pandemic. It was researched which form of feedback is better. However, a few studies have been made on how pedagogy students understand what constitutes good feedback. 23 students of pedagogy who are future teachers in schools or kindergartens participated in the research for this paper. The data was collected in January-March, 2021. This is a qualitative study, based on the methodological approaches of social constructivism.When analyzing the peculiarities of good feedback identified by pedagogy students, we can distinguish the following subcategories: creating a pleasant, safe and benevolent environment; positive effects; helping or encouraging self-assessment; clear feedback; other observations. Future educators, when talking about good feedback, paid attention to the emotional, benevolent environment being created during the feedback; methodological aspects of providing feedback (clear recommendations for improvement, encouraging self-assessment), but did not mention the appropriate choice of the type of feedback at all.